LITERASI KEUANGAN ISLAM DAN FAKTOR-FAKTOR YANG MEMPENGARUHINYA - Any Eliza (Sekolah Tinggi Ilmu Ekonomi AMM, 2019)
This study aims to analyze the level of Islamic financial literacy in lecturers and employees of the Faculty of Economics and Islamic Business Raden Intan Lampung State Islamic University and analyze the influence of psychosocial factors such as the level of religiosity, financial satisfaction and hopelessness towards the level Islamic financial literacy in lecturers and employees of the Faculty of Economics and Islamic Business UIN Raden Intan Lampung. The population in this study were all lecturers and employees of the Faculty of Economics and Islamic Business Raden Intan Lampung State Islamic University T.A. 2017/2018, 50 people. The sampling technique used was purposive sampling, with a number of selected samples of 45 people. Data was collected using questionnaires and documentation. The analytical tool used to prove the hypothesis is the t test and F test. The results of the study show that the level of Islamic financial literacy of lecturers and employees of the Faculty of Economics and Islamic Business UIN Raden Intan Lampung is high. The results of the t statistical test show that the hopelessness variable statistically with α = 5% has a negative and significant influence on Islamic financial literacy (sig. 0.046 <from 0.05). Thus, H1 is accepted. Religiosity variables statistically with α = 5% do not have a significant effect on Islamic financial literacy (sig. 0.220> from 0.05). Thus, H2 is rejected. Statistically, financial satisfaction variable with α = 5% has a positive and significant influence on Islamic financial literacy (sig. 0.011 <from 0.05). Thus, H3 is accepted. The results of the F test were statistically significant with α = 5% show that variable hopelessness, religiosity, and financial satisfaction together have an effect on Islamic financial literacy.